P13 Association of prenatal and postnatal smoking and alcohol consumption on birth weight in the white British population in Bradford: preliminary findings from the born in Bradford study. (16th November 2010) - Petherick, E; Parslow, R; McKinney, P; Tufnell, D; Leon, D; Raynor, Pauline; Lawlor, D; Wright, J
Abstract : Background: Exposure to cigarette smoke and heavy alcohol consumption has been known to influence birth weight and risk of being small for gestational age. Despite this knowledge, very little exploration of the timing of cigarette smoking and alcohol exposure on growth has been undertaken. Aims: To investigate the effect of dose and timing of pre-pregnancy and prenatal alcohol and cigarette exposure on birth weight. Methods: The Born in Bradford cohort includes women of diverse ethnicities, with 46% of the population being of South Asian origin. However, smoking prevalence (5.9%) and alcohol consumption rates (0.4%) in pregnant women of South Asian origin were too low for meaningful analyses. Therefore, analyses were restricted to the white British women who had completed a questionnaire and had a live singleton full-term birth at the Bradford Royal Infirmary, between October 2007 and August 2009. Data were available on smoking and alcohol consumption at three different time points: in the 3 months prior to pregnancy, first 3 months of pregnancy and when the baseline questionnaire was administered (26–28 weeks gestation) by trained interviewers. This information was used to classify women into three mutually exclusive categories separately for both smoking and alcohol: smoker/drinker at all time points, decreasing or quitting at different time periods throughout and nonsmokers/drinkers at all time points. Mean differences in birth weight between these categories were investigated using multivariable linear regression. The model adjusted for maternal age, baby's gender, parity, area deprivation, caffeine consumption, and mother's weight at her first antenatal clinic appointment. Results: 1933 white British mothers and their children were eligible for inclusion. 39.7% were regular smokers in the 3 months prior to pregnancy and 33.6% during pregnancy, whilst 72% consumed alcohol in the 3 months prior to pregnancy and 40% during pregnancy. 29.3% of pregnant women both smoked and drank before pregnancy reducing to 15.1% during pregnancy. Adjusted analysis showed that birth weight was negatively associated with continual smoking, −231 g (95% CI −318.3 to −144.5), whilst quitting or decreasing smoking was associated with −68.5 g reduction (95% CI −119.7 to −17.4) compared to nonsmokers. No association with birth weight was observed for alcohol consumption (−0.16 g, 95% CI −69.9 to 69.6). Conclusions: Timing of quit smoking interventions should concentrate on the pre-pregnancy period to ensure optimal benefits on birth weight. These results suggest that smoking cessation advice provided in the ante natal period may have limited benefit.